2021
DOI: 10.7759/cureus.19004
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Vertebral Fracture in a Patient With Transforaminal Lumbar Interbody Fusion: A Rare Complication

Abstract: Transforaminal lumbar interbody fusion (TLIF) offers the potential benefits of anterior and posterior column decompression and fusion. Pseudarthrosis and infection are among the most common perioperative complications. Vertebral fracture after TLIF is a rare and unusual complication. A 74-year-old female underwent L3-5 TLIF for lumbar spondylolisthesis that caused back pain and neurogenic claudication. She recovered well after surgery. However, she subsequently experienced progressive back pain and recurrent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Chiang et al 14 reported a case of L5 vertebral fracture and L5–S1 spondylolisthesis at 3 months after L3–5 transforaminal lumbar interbody fusion (TLIF). Their case was similar to ours in terms of fracture type and the complication of L5–S1 spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiang et al 14 reported a case of L5 vertebral fracture and L5–S1 spondylolisthesis at 3 months after L3–5 transforaminal lumbar interbody fusion (TLIF). Their case was similar to ours in terms of fracture type and the complication of L5–S1 spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The remaining three cases had pedicle fractures within the fusion range without implant removal, but all of them had experienced middle to long posterolateral fusion (PLF) using a hook-and-rod system with no use of pedicle screws. [11][12][13] Chiang et al 14 reported a case of L5 vertebral fracture and L5-S1 spondylolisthesis at 3 months after L3-5 transforaminal lumbar interbody fusion (TLIF). Their case was similar to ours in terms of fracture type and the complication of L5-S1 spondylolisthesis.…”
Section: Discussionmentioning
confidence: 99%